Outcome of retrograde intrarenal surgery and percutaneous nephrolithotomy in a tertiary care teaching hospital - Regmi, Prabodh; Yogi, Nabin; N Shah, Jay (Journal of Chitwan Medical College, 2025)
Introduction: The PCNL and RIRS are widely used procedures for the treatment of upper urinary tract stones. Method: This retrospective study was carried out in the Department of Urology, Rapti Academy of Health Sciences, Dang, Nepal. Ethical approval was obtained. Patient charts were reviewed for from 01 Aug 2023 to 30 Jul 2024 Microsoft Excel and IBM SPSS were utilized for the parameters such as age sex, stone, and tract size, duration of surgery, and postoperative outcomes (stone clearance rate, length of hospital stay, haemoglobin loss, blood transfusion rate, fever and any additional endoscopic, radiological, or surgical procedures), using descriptive statistics (numbers and frequencies), and their relationships were assessed using the Chi-squire / Fisher's extract test. A p-value of ≤0.05 was considered statistically significant. Result: In the present study, the renal stones were most common in the 30–39-year age. There was a predominance of female sex, and right-sided location of stone. The majority of patients in both groups had stones smaller than 20 mm. RIRS with TFL had a shorter hospital stay (p=0.00001), lower haemoglobin loss (p=0.000016). The stone-free rate (SFR) was 28/31 (90.32%) in the RIRS with TFL group and 35/41 (85.36%) in the PCNL with PL group (p=0.07). Conclusion: The PCNL with PL and RIRS with TFL had similar operative times and were equally effective in achieving stone clearance for upper urinary tract stones up to 3 cm in size. However, PCNL with PL was associated with greater haemoglobin loss and longer hospital stays.